Searching for life : the Grandmothers of the Plaza de Mayo and the disappeared children of Argentina. - Arditti, Rita (University of California Press, 1999)
"An acute and impassioned observer, Rita Arditti describes Argentina's 'dirty war' years and the heroic struggle of a group of Argentine grandmothers who set out, against all odds, to trace the whereabouts of their disappeared children and grandchildren. Admirably comprehensive, Searching for Life reminds us how ordinary citizens can stand up to tyranny and prevail. Even today, the evidence collected by this tenacious group of detectives has led to the arrest of one of the military junta leaders, General Jorge Videla. The Grandmothers of the Plaza de Mayo are truly the unsung heroes of our time." Eric Stover, Director, Human Rights Center, University of California, Berkeley "At last, the long-awaited story of the Grandmothers of the Plaza de Mayo, the group of courageous women children disappeared during the "dirty war," and who have been searching for their missing grandchildren ever since. Refusing to forget, they have transformed their memory into justice and life. Searching for life es the inspiring and moving story of their stubborn resistance to military power, their determination to locate their missing grandchildren, and their extraordinary efforts to identify them." Marysa Navarro, coauthor of Evita: The Real Life of Eva Peron and coeditor of the Reader´s companian to U.S. Women´s History. "The power of RIta Arditti's Searching for Life lies in its thorough, incontrovertible information, and the irrefutable condition of historical truths. Her book is living, faithful and incorruptible monument that protects us against the dangers of forgetting. Her account is an indispensable weapon for those of us who have been protagonists, and as a way to awaken those who were spectators and those who have opted for the comforts of blindness". Alicia Kozameh, author of Steps Under Water. Rita Arditti is part of the Core Faculty at the College of Graduate Studies of the Union Institute. She is coeditor of Test-Tube Women- What future for Motherbood? (1984) and Science and Liberation (1980).